Searching for heavy neutral leptons coupled to axion-like particles at the LHC far detectors and SHiP - Zeren Simon Wang; Yu Zhang; Wei Liu (Journal of High Energy Physics)
Abstract In hidden-sector models, axion-like particles (ALPs) can couple to heavy neutral leptons (HNLs), leading to rich phenomenologies. We study ALPs produced from D- and B-meson decays via quark-flavor-violating couplings, and decaying exclusively into a pair of HNLs which mix with active neutrinos. The ALP can be either short- or long-lived, depending on the masses of the ALP and the HNL, as well as the corresponding coupling strength. Such GeV-scale HNLs are necessarily long-lived given the current bounds on their mixing parameters. We assess the sensitivities of the LHC far detectors and SHiP, to the long-lived HNLs in such theoretical scenarios. We find that for currently allowed values of the ALP couplings, most of these experiments can probe the active-sterile-neutrino mixing parameters multiple orders of magnitude beyond the present bounds, covering large parameter region targeted with the type-I seesaw mechanism. In addition, our results show that compared to the case of a promptly decaying ALP, assuming an ALP of longer lifetimes weakens the sensitivities of the considered experiments to the long-lived HNLs.